The Influence of Acacia Parasite Filtrate as Bioinsecticide for Bagworms (Methane Plana) - Murod, Makmun; Ainurrohmah, Cicik; Nufus, Hayatin (Biosfer: Jurnal Tadris Biologi, 2020)
Dendrophthoe pentandra is a plant parasite that can be detrimental to the host plant and attacks various types of trees, such as acacia. The purpose of this study was to examine the effects and determine the concentration of acacia parasite filtrate on bagworms. This research was an experimental study which used 0%, 20%, 40%, 60%, 80%, and 100% parasite filtrate concentrations. The study employed the Completely Randomized Design method with ANOVA as the method of analysis. Based on the results of phytochemical tests, the parasite filtrate contained alkaloids, flavonoids, saponins, triterpenoids, phenolics, and tannins. The ANOVA test results showed that the concentration of acacia parasite filtrate affected the mortality of the bagworms. Furthermore, based on Duncan's test, the most effective concentrations to be applied were 80%, 60%, and 100%.